Gene therapy of the central nervous system: from bench to bedside - Kaplitt, Michael G. (Academic Press, 2006)
SECTION I. GENE TRANSFER TECHNOLOGY AND REGULATORY ISSUES -- 1. Design and optimization of expression cassettes including promoter choice and regulatory lements -- 2. Identification of Novel AAV Serotypes for Use as Vectors -- 3. HSV amplicon vectors for gene delivery to the nervous system -- 4. Influence of the immune system on CNS gene transfer -- 5. Targeted induction of endogenous neural stem and progenitor cells: A new strategy for gene therapy of neurological disease -- 6. Neurosurgical Targeting, Delivery and Infusion of Gene Therapy Agents in the Brain -- 7. Gene Transfer for Neurological Disease: Agencies, Policies and Process -- SECTION II. GENE THERAPY FOR DEGENERATIVE AND FUNCTIONAL DISORDERS -- 8. Gene therapy for Parkinsons disease -- 9. Non human primate models for testing gene therapy for neurodegenerative disorders -- 10. Delivery of Molecular Therapeutics into the CNS and their Distribution within the Brain -- 11. Gene therapy for CNS diseases using intrabodies -- 12. Gene therapy for epilepsy -- SECTION IIII. PSYCHIATRIC AND BEHAVIORAL GENE THERAPY -- 13. Genetic manipulation of learning and memory -- 14. Psychiatric applications of viral vectors -- 15. Use of viral vectors to influencebehavior -- SECTION IV. GENE THERAPY FOR PAIN AND SPINAL CORD DISEASES -- 16. Herpes simplex vector mediated gene transfer to the peripheralnervous system for the treatment of polyneuropathy and chronic pain -- 17. Characterization of pain receptors in the spinal cord using a viral vector for spatial-temportal gene targeting -- 18. Viral vector mediated gene therapy of pain -- 19. VEGF, an angiogenic factor with neurotrophic activity, useful for treatment of ALS? -- 20. Viral Vector Axonal Uptake and Retrograde Transport: Mechanisms and Applications -- 21. Gene therapy for spinal cord injury -- V. GENE THERAPY FOR BRAIN TUMORS AND NEUROGENETIC DISEASES -- 22. Prodrug-Activation Gene Therapy -- 23. Clinical trials of gene therapy for Canavan Disease -- 24. Gene therapy for the late infantile form of Batten disease -- 25. Molecular Imaging of Gene Therapy for Neurogenetic Diseases
Includes bibliographical references and index. - Description based on print version record
Keywords: Electronic books